Analisis Yuridis Kewenangan Presiden Dalam Penunjukan Kepala Otorita Ibu Kota Negara - Muhammad Rizky Lazuardito; Ahmad Sadzali (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This study discusses the Juridical Analysis of the President's Authority in Appointing the Head of the State Capital Authority. The direct appointment of the Head of the State Capital Authority by the President has opened up the opportunity for regional heads to be appointed by the President again as in the New Order era, where the heads of level I regions were appointed by the President from among the candidates proposed by the Regional People's Legislative Assembly concerned. The formulation of the problem to be examined in this study is what is the position of the head of the IKN authority in the state administration system in Indonesia? And is the president's authority in appointing the head of the IKN authority in accordance with the provisions of the 1945 Constitution? This research is a normative juridical research, the approach is carried out using a statutory approach. The results of this analysis are that the position of the head of the IKN authority in the constitutional system in Indonesia when referring to constitutional provisions can at least refer to the term governor if the IKN is categorized at the provincial level. In addition, the president's authority in appointing the head of the IKN authority based on the provisions of the 1945 Constitution is in accordance with the provisions of the 1945 Constitution, even though the appointment of the Head of the IKN authority is not democratically elected through direct election by the people or people's representatives.